Hyperthermia intravesical chemotherapy acts as a promising alternative to bacillus Calmette–Guérin instillation in non-muscle-invasive bladder cancer: a network meta-analysis - Zeng, Na; Xu, Meng-Yao; Sun, Jian-Xuan; Liu, Chen-Qian; Xu, Jin-Zhou; An, Ye; Zhong, Xing-Yu; Ma, Si-Yang; He, Hao-Dong; Xia, Qi-Dong; Wang, Shao-Gang (Frontiers in Oncology, 2023)
With the shortage of bacillus Calmette-Guérin (BCG) vaccine, it is urgent to find an alternative to BCG instillation, which is the most commonly used adjuvant treatment for non-muscle-invasive bladder cancer (NMIBC) patients after transurethral resection of bladder tumor treatment (TURBt) to delay tumor recurrence. Hyperthermia intra-vesical chemotherapy (HIVEC) with mitomycin C (MMC) is a potential treatment choice. We aim to compare HIVEC with BCG instillation for the preventive efficacy of bladder tumor recurrence and progression. A network meta-analysis (NMA) was taken with MMC instillation and TURBt as the attached comparators. Randomized controlled trials (RCTs) with NIMBC patients after TURBt were included. Articles with pure BCG unresponsible patients and combined therapies were excluded. It was found that HIVEC played a nonsignificant 22% relative reduction in bladder tumor recurrence compared with BCG instillation (HIVEC vs. BCG: HR 0.78, 95% credible interval [CrI] 0.55–1.08), and a nonsignificant higher risk of bladder tumor progression (BCG vs. HIVEC: HR 0.77, 95% credible interval [CrI] 0.22–3.03). HIVEC is a potential alternative to BCG and it is expectable to be standard therapy for NMIBC patients after TURBt during the global shortage of BCG.